Vδ1 T-cell subset appears to be responsive to PD-1 blockade therapy and is associated with survival in melanoma - Herold, Nicola; Bochem, Jonas; Leyens, Johanna; Wingerter, Svenja; Forchhammer, Stephan; Spreuer, Janine; Deseke, Malte; Yurttas, Can; Nocerino, Paola; Reis, Rita Antunes dos; Amaral, Teresa; Wagner, Nikolaus B.; et al. (Journal for ImmunoTherapy of Cancer, 2026)
Background Although most studies of anticancer T-cell immunity focus on αβ T cells, γδ T cells are attracting increasing attention due to their involvement in antitumor immune responses in various cancer entities, including melanoma. While immune checkpoint blockade (ICB) using the antagonistic programmed cell death protein 1 (PD-1) antibodies nivolumab and pembrolizumab significantly improved the survival of patients with melanoma with distant metastasis, prognosis remains poor. PD-1 is not only expressed by αβ T cells but also by γδ T cells, making this numerically minor population of unconventional T cells, whose role in melanoma is still elusive, a target of ICB.Methods Here, we present a detailed γδ T-cell profiling study in late-stage melanoma at single-cell level using mass and polychromatic flow cytometry, T-cell receptor repertoire analyses and immunohistochemistry.Results Our analyses link high frequencies of peripheral Vδ1 T cells before the start of anti-PD-1 therapy to a significantly reduced overall survival. In these patients, the Vδ1 compartment is dominated by a late-differentiated senescent-like phenotype that is presumably unresponsive to therapy. This phenotype is less prevalent at the tumor site and analysis of RNA sequencing data revealed that the abundance of Vδ1 T cells within the tumor was positively associated with survival.Conclusions Our study suggests that Vδ1 T cells are associated with clinical outcomes, with a responsive subset expanding under ICB in patients where such a response remains possible. The observed clinical effects may be supported by the infiltration of these cells into the tumor, where they contribute to cancer immunosurveillance.